Optimization study of the main parameters of different types of wind turbine generators* This work was supported in part by the National Natural Science Fund under Grant 52071090, in part by the Doctoral Start-up and Postgraduate Fund under Grant R17062, and in part by the Young Innovative Talents in Colleges and Universities of Guangdong Province under Grant 2019KQNCX046. (4th February 2022) - Xu, Yuanyuan; An, Lian-Tong; Jia, Xiao-Ping; Jia, Bao-Zhu; Maki, Naoki
Abstract: The research and development of large-scale wind turbine generators have become a future trend in green renewable energy field from the dual perspectives of the environment and economics. In this work, an electrical design method is first proposed and applied to different types of wind turbine generators, including the high-temperature superconducting (HTS), the permanent magnet, and the traditional copper generators. The optimal electrical designs of the three types of 10 MW wind turbine generators are then created based on the developed design program. Second, the influences of the rated revolution on the basic performance parameters of the HTS generator are investigated, and the results are compared with those of the other two types of generators. It is found that the generator weight decreases with the increases of the rated revolution and the stator outer diameter, and the optimal rated revolution for a generator with a large stator outer diameter is determined to be 40 min −1 . Moreover, the weight of the field parts is found to have the same regulation rule as the generator weight. Finally, the design results of the three types of wind turbine generators are comparatively discussed, and it is found that the HTS wind turbine generator is superior to its two counterparts.